(untitled) (City Dental College Journal, 2018)
Aims: Degenerative joint diseases and decreased bone mass i.e. osteoporosis are two common age related skeletal disorders responsible for pain and disability. Bangladesh has a high incidence of osteoporosis and the incidence particularly in women, occurs among a relatively younger age group than in the developed world. However little is known about the correlation between degenerative changes and osteoporosis in lumbar spine of elderly women. The purpose of this study was to clarify this relationship in elderly women of Dhaka, Bangladesh. Methods: A cross-sectional study was conducted at the department of radiology and imaging of Bangladesh institute of research and rehabilitation in diabetes, endocrine and metabolic disorders (BIRDEM), Dhaka during the period of 1st January, 2009 to 31st December, 2010. DEXA scan of spine and BMD measurement were done at a renowned private hospital of Dhaka. Total 63 elderly female aged between 50-75 years were randomly selected for this study. Results: An inverse relationship between osteoporosis and spondylosis in postmenopausal women as evaluated by bone mineral density and semiquantitative scoring of spinal degeneration was observed. A significant negative correlation (r=-0.53:p<0.05) was found between T-score and grade. DOI: http://dx.doi.org/10.3329/cdcj.v10i1.13740 City Dent. Coll. J Volume-10, Number-1, January-2013